Mechanism of skin whitening through San-Bai decoction-induced tyrosinase inhibition and discovery of natural products targeting tyrosinase. Issue 13 (31st March 2023) - Li, Liyuan; Tang, Yiran; Li, Xin; Zhou, Tao; Song, Qiuhang; Li, Aiying
Abstract : Melanin deposition is the main cause of skin darkening, which can lead to severe physical and psychological distress, necessitating the development of approaches for preserving skin health and fairness. Tyrosinase (TYR) is the rate-limiting enzyme in melanin synthesis, and its activity directly determines the degree of melanin accumulation in the skin, which in turn affects skin color. Currently, TYR inhibitors derived from natural products are widely used for skin whitening. San-Bai decoction (SBD) is effective for skin whitening and softening, but its mechanism of action, efficacy and high efficiency TYR inhibitors for skin whitening remain poorly understood. Here, we employed systems biology and network pharmacology to analyze the active compounds and targets of SBD, using the follow databases: TCMIP, TCMID, and BATMAN-TCM. Construct a molecular network centered on the regulation of TYR by SBD in skin whitening, using STRING database and cytoscape. Enrichment analysis using KOBAS database and ClusterProfiler. Virtual screening of candidate TYR inhibitors using Molecular Operating Environment software and Amber 18 software. SBD may act through tyrosine metabolism, melanogenesis, and other signaling pathways to regulate TYR activity and inhibit melanogenesis. We identified TYR and ESR1 as possible key targets for the whitening effect of SBD and screened out pentagalloylglucose, 1, 3, 6-tri-O-galloyl-beta-D-glucose, 1, 2, 4, 6-tetragalloylglucose, and liquiritigenin 4′, 7-diglucoside as inhibitors of TYR, in addition to glycyrrhizic acid, pachymic acid methyl ester, nicotiflorin, gamma-sitosterol, and isoliensinine as inhibitors of ESR1. We also performed virtual drug screening of a library of natural small-molecule compounds (19, 505 in total) and screened out lycopsamine, 2-phenylethyl b-D-glucopyranoside, and 6-beta-hydroxyhyoscyamine as inhibitors of TYR. We identified natural compounds with the potential for skin whitening through inhibition of TYR, thus advancing research on SBD and its applications.